2019
DOI: 10.1108/etpc-05-2019-0068
|View full text |Cite
|
Sign up to set email alerts
|

Opening spaces of restoration for youth through community-engaged critical literacy practices

Abstract: Purpose The purpose of this paper is to explore how critical literacy practices within a community youth program opened spaces for restoration for youth. In turn, youth created civic conversations about race, juvenile justice and school discipline inequities to enact change within their community. Design/methodology/approach This qualitative study used ethnographic methods such as interviews and observation to collect data from youth, community members and adults who run the youth center. Data were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The ART managed to respond to (though not dispel) these difficulties by leaning into and adapting the communicative practices—norms, routines, and “joy-bringers”—they had relied upon in past face-to-face gatherings (Hadley et al, 2019; Wright et al, 2020). They were adamant, in other words, about taking time to establish trust and build a sense of community upfront with youth outside the ART who were in attendance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ART managed to respond to (though not dispel) these difficulties by leaning into and adapting the communicative practices—norms, routines, and “joy-bringers”—they had relied upon in past face-to-face gatherings (Hadley et al, 2019; Wright et al, 2020). They were adamant, in other words, about taking time to establish trust and build a sense of community upfront with youth outside the ART who were in attendance.…”
Section: Resultsmentioning
confidence: 99%
“…They were selected through an application and interview process. Indeed, one of the newcomers had first learned of the ART as a workshop participant the year before; it is this very ethic of civic cultivation, of reaping and sowing “a harvest of savvy, community-engaged youth” (Hadley et al, 2019, p. 3), that perhaps best demonstrates the enduring contributions of the Yamacraw Center to the surrounding community and the city at large. The new members were McKinley, Martens, and Bea, all three of whom were Black, cisgender young women, and Clavel, a white, cisgender young woman.…”
Section: Methodsmentioning
confidence: 99%
“…Less attention, however, has been given in the literature to the role of youth researchers in training other youth researchers, aside from glancing references to the value of having returning youth researchers return to continued iterations of ongoing YPAR projects (Morrell 2008) or the ongoing culture of inquiry that is created in YPAR spaces with longevity. In fact, we ourselves have noted this culture of inquiry in relation to the Yamacraw Center in other spaces (Burke and Hadley 2018;Hadley et al 2019).…”
Section: Literature Reviewmentioning
confidence: 93%
“…The center is beholden first and foremost to the local community and those within it who have historically been short-changed by gentrification connected to systemic and historic racism and excluded from decision-making processes because of racialized identity, ethnicity, class, gender, and/or age. Yamacraw youth, importantly, are not sheltered from these realities but are instead coached in restorative practices and complex systems-change processes by way of response and in search of healing (Burke and Hadley 2018 ; Hadley et al 2019 ). Through a host of critical literacy and arts-based inquiry practices, they acquire the skills and necessary savvy to seek out unheard voices and ask hard questions about the official and unofficial narratives of their city, experiences that then give them the foundation from which to critique narratives of colonial progress, advocate for policy change, and imagine more-just futures for themselves and their communities.…”
Section: The Yamacraw Centermentioning
confidence: 99%
“…Such perspectives are rooted in the work of John Dewey (1916) and Paulo Freire (1970), who promoted the idea that schools should teach about democratic society and engage children in debate about fundamental notions such as equality and justice. Studies have shown that humanities-based approaches to K-12 education can help disadvantaged youth improve their performance on content-area standards while also understanding themselves through their relationship with the people in their community (e.g., Hadley, Burke, & Wright, 2019;San Pedro, 2016).…”
Section: Introductionmentioning
confidence: 99%